2003
DOI: 10.1080/ejc.8.3.129.134
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the modification of sexual desire of users of oral hormonal contraceptives and intrauterine contraceptive devices

Abstract: Sexual desire does not vary in relation to the use of OCs or IUDs, yet it does decrease with age, in nulliparous women and in those with an average or poor relationship with their partner. Furthermore, sexual desire shows an increase between the first 6 and 12 months of contraceptive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…For those who do report an adverse impact, consideration of another method is warranted, but switching to a different pill or delivery system may be fraught with problems as the reduction in sexual activity may not be the result of OC initiation, but rather the social, relationship, or psychological issues affecting other aspects of her life. As demonstrated by Martin-Loeches et al [ 10 ], age and poor relationships and not contraceptive use were associated with an adverse effect on sexuality. The clinician who hears that a patient who recently began OCs is unhappy with its impact on sexuality is well advised to question about family, relationship, social and psychological issues, as well as general health and well-being issues, before switching a woman to another method.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…For those who do report an adverse impact, consideration of another method is warranted, but switching to a different pill or delivery system may be fraught with problems as the reduction in sexual activity may not be the result of OC initiation, but rather the social, relationship, or psychological issues affecting other aspects of her life. As demonstrated by Martin-Loeches et al [ 10 ], age and poor relationships and not contraceptive use were associated with an adverse effect on sexuality. The clinician who hears that a patient who recently began OCs is unhappy with its impact on sexuality is well advised to question about family, relationship, social and psychological issues, as well as general health and well-being issues, before switching a woman to another method.…”
Section: Discussionmentioning
confidence: 80%
“…However, Martin-Loeches et al [ 10 ] did fi nd that a decrease in desire was signifi cantly associated with age and an average to poor quality of relationship. Similarly, Dennerstein et al [ 12 ] found that prior function and relationship factors were more important than hormonal determinants of sexual function in women going through the menopausal transition.…”
Section: Basis Of Concern: Biologic Plausibilitymentioning
confidence: 96%
See 1 more Smart Citation
“…Sabatini et Cagiano (2006) vont également dans le sens de différence en fonction du progestatif utilisé. Aussi, l'étude de Martin-Loeches et al (2003) ne montre pas de baisse significative de l'évolution du désir et la méta-analyse de Davis et Castaño (2004) montre un désir inchangé globalement. Enfin, Burrows et al (2012) concluent son article stipulant que bien qu'une majorité de femmes ont une sexualité inchangée avec la mise en place de la COP, certaines ont une altération de leur sexualité qu'il faut prendre en compte et entendre.…”
Section: Discussionunclassified
“…Moreover, it is also nonhormonal, so it does not have any hormone-related side effects or contraindications, and it does not affect breastfeeding. There is also no evidence to suggest that the copper IUD is associated with weight gain, altered libido, or mood changes [14,15]. Although the effectiveness of IUDs is excellent, they may have some adverse events associated with IUD use, including perforation and an increased infection immediately following insertion [15].…”
Section: Discussionmentioning
confidence: 99%